Stress during Adolescence Increases Novelty Seeking and Risk-Taking Behavior in Male and Female Rats - Toledo, Maria; Sandi, Carmen (Frontiers in Behavioral Neuroscience, 2011)
Adolescence is a period of major physical, hormonal and psychological change. It is also characterized by a significant increase in the incidence of psychopathologies and this increase is gender-specific. Likewise, stress during adolescence is associated with the development of psychiatric disorders later in life. Previously, using a rat model of psychogenic stress (exposure to predator odor followed by placement on an elevated platform) during the pre-pubertal period (postnatal days 28-30), we reported sex-specific effects on auditory and contextual fear conditioning. Here, we study the short-term impact of psychogenic stress before and during puberty (postnatal days 28-42) on behavior (novelty seeking, risk taking, anxiety and depression) and hypothalamus-pituitary-adrenocortical (HPA) axis activation during late adolescence (postnatal days 45-51). Peri-pubertal stress decreased anxiety-like behavior and increased risk taking and novelty seeking behaviors during late adolescence (measured with the elevated plus maze, open field and exposure to novel object tests and intake of chocopop pellets before or immediate after stress). Finally neither depressive-like behavior (measured at the forced swim test) nor HPA response to stress (blood corticosterone and glucose) were affected by peri-pubertal stress. Nevertheless, when controlling for the basal anxiety of the mothers, animals exposed to peri-pubertal stress showed a significant decrease in corticosterone levels immediate after an acute stressor. The results from this study suggest that exposure to mild stressors during the peri-pubertal period induces a broad spectrum of behavioral changes in late adolescence, which may exacerbate the independence-building behaviors naturally happening during this transitional period (increase in curiosity, sensation-seeking and risk taking behaviors).